Contributing Factors to Maritime Accidents (British Journal of Multidisciplinary Studies, 2026)
This study assessed seafarers' perceptions of the contributory factors to maritime accidents at the Protect Marine Deck and Engine Officers' Training and Assessment Center in Carcar City, Cebu, Philippines. The findings served as the basis for a proposed action plan to enhance maritime safety practices. Specifically, the study determined the respondents' profile in terms of age, sea expérience, civil status, educational attainment, and type of vessel boarded; examined their perceptions on the extent of contributory factors to maritime accidents in terms of human, technical, environmental, operational, structural and design, management and regulatory, and piracy and security risks; identified the significant relationship between respondents' profile and their perceptions; and developed an action plan based on the results. The descriptive-correlational research design was employed using a researcher-made questionnaire administered to seafarers enrolled in safety training courses. Frequency counts and percentages were used to describe the respondents' profile; the weighted mean determined the extent of perceived contributory factors; and the chi-square test with Pearson's Contingency Coefficient C measured the significance and strength of relationships between variables. Findings revealed that most respondents were aged 30–49 years, married, had 1–5 years of sea experience, were college graduates, and were assigned to bulk carrier vessels. Human, operational, and management and regulatory factors were perceived as high, particularly fatigue due to long working hours, poor decision-making during critical operations, and weak enforcement of safety policies. Technical, environmental, structural, design, piracy, and security risk factors were perceived as moderate, with equipment failure, adverse weather conditions, ageing vessel components, and a lack of anti-piracy training identified as notable concerns. Statistical analysis showed that only age and vessel type were significantly associated with the selected contributory factors. Age was moderately associated with human factors, while vessel type was moderately associated with structural and design factors. The study concluded that maritime accidents were primarily attributable to human factors, operational lapses, and management weaknesses. It emphasized the need for targeted safety interventions that consider age-related factors and vessel-specific structural conditions to strengthen maritime accident prevention strategies.